Peran Soft Skill dan Hard Skill dalam Peningkatan Kualitas Guru Pendidikan Agama Kristen Di Era 5.0 - Rut Frida Hastuti Nduru; Nehemia Nome (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The 5.0 era is marked by rapid technological advances and social changes, affecting various aspects of life, including the field of education. Christian religious education plays an important role in shaping the character and morals of the younger generation. But in reality, the lack of emphasis on developing soft skills can be a problem, because the teacher's ability to interact empathetically, have creativity, leadership, and adaptability becomes very important in guiding students in a spiritual, moral, and emotional context. In addition, an excessive focus on hard skills, such as understanding theology and religious practice, can ignore the importance of developing soft skills in dealing with the changes faced in the 5.0 era. In this study, the authors used a literature study, therefore to achieve the objectives of this study, superior teacher quality was needed, which had a balance between software and hardware. The purpose of this study is to present software and hardware in improving the quality of Christian religious education teachers in the 5.0 era. Soft skills include interpersonal, communication, leadership, empathy, and adaptability skills, which support teachers in interacting with students, colleagues, and a changing environment. While hard skills include specific knowledge, information technology, teaching methodology, as well as expertise in the field of Christianity.